2016
DOI: 10.1111/afe.12166
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of resource distribution among conspecific larvae in two fruit fly species: Anastrepha fraterculus and Ceratitis capitata (Diptera: Tephritidae)

Abstract: Anastrepha fraterculus (Diptera: Tephritidae) and Ceratitis capitata (Diptera: Tephritidae) are fruit fly pests whose larvae are frequently found sharing the same fruit with conspecifics. Because larvae are incapable of leaving the fruit in search of non‐infested fruit, they are forced to share nutritional resources and eventually compete with other larvae for these. In the present study, we investigated the effect of intraspecific competition on the development of A. fraterculus and C. capitata larvae, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…An increase in density negatively affected the pupal weight, which, in most insects, is correlated with the size of the adults and their overall reproductive success (Quiring & McNeil, 1984;Averill & Prokopy, 1987;Liedo et al, 1992;Honěk, 1993;Allen & Hunt, 2001;Dukas et al, 2001;Nufio & Papaj, 2004;Navarro-Campos et al, . For C. capitata, only a small decrease in pupal weight and pupal survival was observed, which may be due to a density-dependent effect and is not necessarily affected by the identity of the competitor species (Liendo et al, 2016). 100% indicates only one species in the patch; 75% indicates 75% of one species and 25% of the other species; 50% indicates 50% of one species and 50% of the other species; 25% indicates 25% of one species and 75% of the other species.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…An increase in density negatively affected the pupal weight, which, in most insects, is correlated with the size of the adults and their overall reproductive success (Quiring & McNeil, 1984;Averill & Prokopy, 1987;Liedo et al, 1992;Honěk, 1993;Allen & Hunt, 2001;Dukas et al, 2001;Nufio & Papaj, 2004;Navarro-Campos et al, . For C. capitata, only a small decrease in pupal weight and pupal survival was observed, which may be due to a density-dependent effect and is not necessarily affected by the identity of the competitor species (Liendo et al, 2016). 100% indicates only one species in the patch; 75% indicates 75% of one species and 25% of the other species; 50% indicates 50% of one species and 50% of the other species; 25% indicates 25% of one species and 75% of the other species.…”
Section: Discussionmentioning
confidence: 83%
“…Each patch consisted of a cylindrical plastic cup (diameter 2.8 cm, height 1 cm) that contained 3.65 g of artificial diet. This diet is regularly used in the artificial rearing of A. fraterculus and it was chosen for the current experiments because previous studies showed that C. capitata is able to successfully develop in this diet as well as A. fraterculus (Liendo et al, 2016). Sodium benzoate and methylparaben were added as preservatives.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Birke et al (2015) mencionan como aspecto fundamental para prevenir la introducción de plagas cuarentenarias, conocer el uso de hospederos por parte de estas moscas; adicionalmente, el uso de hospederos por tefrítidos y su competencia inter e intra específica es un tema que se ha estudiado a nivel de ensayos en campo y laboratorio (Duyck et al, 2004 Segura et al, 2006;Devescovi et al, 2015;Lopes et al, 2015;Liendo et al, 2016). Cuando los tefrítidos invaden nuevas áreas, se puede presentar competencia jerárquica o coexistencia estable con especies preestablecidas.…”
Section: Introductionunclassified